2012
DOI: 10.1159/000337932
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Safety and Efficiency of Five Percutaneous Kidney Biopsy Approaches of Native Kidneys: A Multicenter Study

Abstract: Background: Renal biopsy (RB) is necessary for the diagnosis, prognosis, and therapy guidance of native kidney diseases. Few studies have compared outcomes of RB procedures. We retrospectively compared the safety and efficiency of five biopsy procedures. Methods: The number of glomeruli on light microscopy (LM) and on immunofluorescence (IF) and serious adverse events following RB performed in five nephrology units (C1–C5) were collected. C1 performed ultrasound (US) assessment before RB and used a 14-gauge co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
4
20
1
Order By: Relevance
“…While there was no major complication during the third decade between 1993 and 2002, the proportion of patients who had minor complications actually increased from 19 to 28% [13]. In a more recent French multicenter trials, the lowest major complication was 0.7% [14]. The rate of major complications in our study was closer to the one reported by Stratta et al [13] than the French research.…”
Section: Discussionsupporting
confidence: 61%
“…While there was no major complication during the third decade between 1993 and 2002, the proportion of patients who had minor complications actually increased from 19 to 28% [13]. In a more recent French multicenter trials, the lowest major complication was 0.7% [14]. The rate of major complications in our study was closer to the one reported by Stratta et al [13] than the French research.…”
Section: Discussionsupporting
confidence: 61%
“…However, in the prospective trial by Nicholson et al [37], no differences in complication rates were found for biopsies performed with 14-, 16- or 18-gauge automated needles. Similarly, a number of other studies have found no differences in complication rates or transfusion requirements based on needle size [4,8,11,21,32,44,45], including the 2013 report of the Norwegian Kidney Biopsy Registry [21] of 9,288 PRBs. However, in a recent meta-analysis by Corapi et al [12], the rate of transfusion was greater in patients biopsied with a 14-gauge automated needle compared to 16- and 18-gauge needles (2.1 vs. 0.5%, p = 0.009), and this led to the recommendation that the use of 14-gauge needles be discouraged.…”
Section: Discussionmentioning
confidence: 88%
“…The number of glomeruli per biopsy was significantly less with the 18-gauge needle (9 glomeruli) compared to that obtained with the 14- or 16-gauge needles (12 glomeruli each, p < 0.001), and the adequacy rate was lower at 94.3%. A number of studies have shown that the diagnostic yield is greater with 14-gauge automated needles compared to 16- or 18-gauge needles, and the quality of the sample has been shown to be superior, with more ‘intact' glomeruli and less ‘crush or fragmentation' artifact [3,8,11,21,29,32,33,34,35,36,37,38]. In the only prospective study assessing the differences between automated needle sizes, Nicholson et al [37] demonstrated that the use of a 14-gauge needle resulted not only in a significantly larger sample size (15 vs. 11 vs. 9 glomeruli, p < 0.05) but also greater diagnostic success (85 vs. 76 vs. 53%, p < 0.05) compared to the use of 16- or 18-gauge needles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous renal biopsy (PRB) of kidney transplants is the standard procedure for obtaining tissue samples (4)(5)(6)(7). However, PRB is associated with an increased risk of complications in patients who have bleeding disorders, are undergoing anticoagulation therapy or suffer from uncontrolled hypertension.…”
Section: Introductionmentioning
confidence: 99%